New insights into polyphyly of the harpacticoid genus Delavalia (Crustacea, Copepoda) through morphological and molecular study of an unprecedented diversity of sympatric species in a small south korean bay. - Karanovic, T. & K. Kim (Zootaxa, 2014)
Polyphyly of the genus Delavalia Brady, 1869 has been postulated previously based on intuitive methods, but no phylogenetic study was ever conducted. A chance discovery of seven sympatric species of this genus in the highly industrialized Gwangyang Bay in South Korea, in addition to one species each from the closely related genera Stenhelia Boeck, 1865 and Onychostenhelia Itô, 1979, prompted a renewed interest in the phylogenetic relationships within the subfamily Stenheliinae Brady, 1880. Additional surveys along the Korean coast failed to produce Delavalia species, but comparative material was sourced from Posyet Bay in the Russian Far East. Aims of this study were to reconstruct phylogenetic relationships of the newly collected stenheliins using molecular methods, test the hypothesized polyphyly of Delavalia, formally describe any resulting monophyletic units, perform a comparative study of traditional morphological and novel micro-morphological characters, and describe all new Delavalia species. A fragment of the mtCOI gene was successfully PCR-amplified from 23 stenheliin specimens and an additional 300 specimens were studied for morphological characters. All phylogenetic analyses supported the presence of at least eight genetically divergent lineages, most with very high bootstrap values, and the polyphyletic nature of Delavalia is demonstrated. Three new genera, each supported by molecular data and a number of morphological synapomorphies, were erected to accommodate the newly discovered species and some previously described members of Delavalia: Wellstenhelia gen. nov., Itostenhelia gen. nov., and Willenstenhelia gen. nov. The Chinese Wellstenhelia qingdaoensis (Ma & Li, 2011) comb. nov. is recorded for the first time in Korea, and six new species are described from Gwangyang Bay: Wellstenhelia calliope sp. nov., Wellstenhelia clio sp. nov., Wellstenhelia erato sp. nov., Wellstenhelia euterpe sp. nov., Itostenhelia polyhymnia sp. nov., and Willenstenhelia thalia sp. nov. Additonally, Itostenhelia golikovi (Chisleno, 1978) comb. nov. is redescribed from newly collected material from the type locality in Russia and its male described for the first time, while Wellstenhelia melpomene sp. nov., Willenstenhelia urania sp. nov., and Willenstenhelia terpsichore sp. nov. are established as new names for previously reported populations of two presumably widely distributed Delavalia species.